Efektivitas Kahoot dalam Pembelajaran Daring Mata Kuliah Kanji Terhadap Mahasiswa Bahasa Asing Terapan - Fitri Alfarisy; Amelia Jannati; Alifina Hamidah Amalia; Mutiara Risko Siagian (Jurnal Pendidikan Indonesia, 2022)
Lecturer learning of Applied Foreign Language students by using a learning kahoot application that presents a quiz in it. Explaining the effectiveness of kahoot media in online lectures for Applied Foreign Language students. This research is a quantitative research with survey method. Methods Survey research deals with questions about one's own beliefs and behavior. Based on the descriptions that have been submitted including: a) Students know what a kahoot application is; b) 70% of students consider kahoot important in learning kanji; c) Overall, most of the students are satisfied with the Kahoot application; d) The learning model with kahoot media produces a positive influence on the concept of student understanding. As the results of the research conducted, it can be concluded that the use of the Kahoot application is quite effective in improving the understanding of kanji courses for Applied Foreign Language students, the application of the Kahoot application is better when learning online in improving the understanding of kanji courses.